Influence of mineral and organic nitrogen on tuber dry matter and specific gravity of potatoes - Rodrigues, M.A. (1998)
Dry matter percentage (DIv1%) is an important qualitative characteristic of potato tubers. Frequently N fertilisation significantly affects DM% but there have been several] studies differing in their results. According to Jenkins and Nelson (1992), numerous published reports indicate a reduction in DM%, others show no effects of N and some recorde instances where final DM% increases significantly as N rate increases. The DM% is normally estimated by the specific gravity (SG), despite some known limitations. The influence of mineral and organic N fertilising on dry matter content of the cv Desirée, the most important variety in Portugal, was studied during three years (1995-1997). For the last two years (1996-1997), specific gravity was also determined. The relationship between the specific gravity and the city matter content of tubers was established and analysed.